IoT smartwatch based on open technologies for the collection of thermal comfort data - Julio Landa; Guillermo Barrios; Guadalupe Huelsz (HardwareX)
This paper presents an IoT smartwatch based on open technologies for thermal comfort data collection. The device performs simplified thermal comfort surveys every hour, collecting data such as clothing insulation level (clo), metabolic activity (met), location, thermal sensation, and thermal acceptance. In addition, it measures two physiological variables: skin temperature and heart rate. The smartwatch is built with low-cost components, including a XIAO ESP32C3 microcontroller, a GY-906 temperature sensor, a MAX30102 heart rate sensor, and Seeed Studio’s XIAO Round Display touchscreen. All collected data are published in real time on an IoT platform that allows remote access to all information. During device registration, the user is prompted to complete a Google Form, where additional data such as gender, age, height, weight, and frequency of air conditioner use are collected. This information, in combination with data from the smartwatch, contributes to a robust database. The ease of use, the design of the device, and its open-source nature make it ideal for the collection of thermal comfort data and its potential use for the generation of adaptative thermal comfort models.